Educação em arte: desmitificando e ampliando concepções estéticas - Camargo, Maria Aparecida Santana (Universidade do Vale do Rio do Sinos, 2007)
This investigation problematizes the paradigms and esthetic conceptions in the ambit of art education, and it was carried out joining Art with History and Sociology. It is based on strong contemporaneousness texts, like the conceptions of Pierre Bourdieu, a critic analist of education. The study is centralized in the knowledge that our teachers bring to the classroom and, conseqüently, in the constitution of their habitus. It departs from the hypothesis that these paradigms are socially built and aims to examine and analyse educational practices in art, identifying in which esthetic paradigms they are enrolled. It is a qualitative nature study, and the investigative route chosen has as its basis both a theoretical and an empiric study. The research was performed through open intervews with art teachers analysing adages and methafors on art and education in art, with students and community that, together with art teachers, are the subjects of this investigation. From a pictorical-historical carving, centered
Education in art: ummytifing and amplifying estethics conceptions
Keywords: estética; sala de aula; educação artística; Ciências Humanas